Lactiplantibacillus plantarum N4 ameliorates lipid metabolism and gut microbiota structure in high fat diet-fed rats - Deng, Manqi; Zhang, Shuaiying; Wu, Siying; Jiang, Qiunan; Teng, Wenyao; Luo, Tao; Ouyang, Yerui; Liu, Jiantao; Gu, Bing (Frontiers in Microbiology, 2024)
Lowing blood lipid levels with probiotics has good application prospects. This study aimed to isolate probiotics with hypolipidemic efficacy from homemade na dish and investigate their mechanism of action. In vitro experiments were conducted to determine the cholesterol-lowering ability of five isolates, with results showing that Lactiplantibacillus plantarum N4 exhibited a high cholesterol-lowering rate of 50.27% and significant resistance to acid (87%), bile salt (51.97%), and pepsin (88.28%) in simulated gastrointestinal fluids, indicating promising application prospects for the use of probiotics in lowering blood lipids. The findings from the in vivo experiment demonstrated that the administration of N4 effectively attenuated lipid droplet accumulation and inflammatory cell infiltration in the body weight and liver of hyperlipidemic rats, leading to restoration of liver tissue morphology and structure, as well as improvement in lipid and liver biochemical parameters. 16S analysis indicated that the oral administration of N4 led to significant alterations in the relative abundance of various genera, including Sutterella, Bacteroides, Clostridium, and Ruminococcus, in the gut microbiota of hyperlipidemia rats. Additionally, fecal metabolomic analysis identified a total of 78 metabolites following N4 intervention, with carboxylic acids and their derivatives being the predominant compounds detected. The transcriptomic analysis revealed 156 genes with differential expression following N4 intervention, leading to the identification of 171 metabolic pathways through Kyoto Encyclopedia of Genes and Genomes enrichment analysis. Notably, the glutathione metabolism pathway, PPAR signaling pathway, and bile secretion pathway emerged as the primary enrichment pathways. The findings from a comprehensive multi-omics analysis indicate that N4 influences lipid metabolism and diminishes lipid levels in hyperlipidemic rats through modulation of fumaric acid and γ-aminobutyric acid concentrations, as well as glutathione and other metabolic pathways in the intestinal tract, derived from both the gut microbiota and the host liver. This research offers valuable insights into the therapeutic potential of probiotics for managing lipid metabolism disorders and their utilization in the development of functional foods.